MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS SISWA MELALUI PEMBELAJARAN CREATIVE PROBLEM SOLVING - Ningsih, Eva Fitria (Lentera: Jurnal Ilmiah Kependidikan, 2021)
This research is motivated by the low mathematical literacy ability of students. To overcome this, research was conducted using Creative Problem Solving (CPS) learning. The purpose of this research was to investigate the effects of CPS learning on mathematical literacy ability. The research method used in this study was quasi-experimental with the type of study design is nonequivalent control group design, then two equal classes were selected in terms of academic ability. Both groups were given a pretest and a posttest. The first class was given special treatment using CPS learning (experimental class) and the second class was not treated or treated with conventional learning (control class). The instrument used in this research is a mathematical literacy ability test. Data processing in this study used the t-test (Independent Sample t-Test). The results of data analysis concluded that the increase in mathematical literacy ability of students who received CPS learning was better than students who received conventional learning.